Strategi Seleksi dan Penempatan Tenaga Kerja di PT. Surya Bakti Utama Medan: Tantangan dan Solusi - Aminuddin Aminuddin (Journal of Islamic Economic and Law (JIEL), 2025)
This study aims to analyze the effectiveness of the employee selection and placement process at PT. Surya Bakti Utama Medan and evaluate its compliance with applicable procedures. Additionally, this research seeks to identify challenges in the recruitment, placement, and promotion system to provide constructive recommendations for improving human resource management within the company. The research employs a descriptive method with a qualitative approach. Data is collected through literature studies and field research using observation techniques and interviews with company managerial staff. The analysis is conducted using descriptive and deductive methods to systematically interpret the findings. The results indicate that the selection process at PT. Surya Bakti Utama Medan includes several essential stages but still has shortcomings, such as the absence of health tests as part of the selection process. Furthermore, employee placement often does not consider the alignment between employees' qualifications and the positions they fill, potentially reducing productivity. Job promotions are also not conducted transparently and are primarily based on personal relationships rather than employee performance and competence. In conclusion, improvements in the selection, placement, and promotion systems are crucial to enhancing the effectiveness of workforce management in the company. By implementing a more objective and competency-based system, PT. Surya Bakti Utama Medan can improve employee productivity and corporate competitiveness.